Penerapan Hukum terhadap Pelaku Tindak Pidana Korupsi secara Bersama-sama - Emmy Evelina Marpaung (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the application of material criminal law and the judge's legal considerations in two corruption cases: Central Jakarta District Court Decisions No. 3/Pid.Sus-TPK/2025/PN Jkt.Pst. and No. 21/Pid.Sus-TPK/2025/PN Jkt.Pst. Conducted within the jurisdiction of the Supreme Court of the Republic of Indonesia, the research uses literature review methods, including laws, court decisions, and related legal literature. The study adopts a descriptive approach to analyze and present findings. Results indicate differing views between the public prosecutor and the panel of judges. The Public Prosecutor believes the defendant is proven guilty under Article 2(1) of Law No. 31/1999 on the Eradication of Corruption (amended by Law No. 20/2001), in conjunction with Article 55(1) of the Criminal Code, Law No. 46/2009 on the Corruption Court, and Law No. 8/1981 on Criminal Procedure. However, a dissenting opinion emerged among the judges. One judge disagreed with the majority, arguing that Judex Facti incorrectly applied the law. The judge emphasized that in cases with alternative charges, the court must evaluate all charges collectively rather than selectively, as in subsidiary charges. Therefore, the judge believed that the charge meeting the legal elements revealed in court should be selected based on comprehensive evaluation. This dissent highlights the legal complexity and interpretive challenges in corruption trials under Indonesian law.